Financial performance comparison: BCA Conventional and BCA Sharia period of 2016-2018 - I Putu Eka Sanjaya; I Dewa Ketut Gede Prabawa (Universitas Pendidikan Nasional, 2023)
This study examined the financial performance of BCA Conventional and BCA Sharia from 2016 to 2018, focusing on six financial ratios: Non-Performing Loans/Non-Performing Financing (NPL/NPF), Loan to Deposit Ratio/Financing to Deposit Ratio (LDR/FDR), Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), and Capital Adequacy Ratio (CAR). BCA Conventional generally outperformed BCA Sharia, showing superior results in LDR, ROA, ROE, and BOPO ratios, indicating better liquidity, profitability, and operational efficiency. BCA Sharia excelled in NPF and CAR ratios, suggesting lower credit risk and better capital adequacy. Both banks met regulatory standards, though BCA Sharia needed improvement in ROA and ROE to enhance competitiveness. The study underscored the importance of continuous performance monitoring and strategic management to maintain stability and trust in the banking sector. Future research should explore more advanced analytical methods and extend comparisons across different types of banks for more comprehensive insights.